2014
DOI: 10.1109/tmm.2014.2342668
|View full text |Cite
|
Sign up to set email alerts
|

Near-Duplicate Subsequence Matching Between the Continuous Stream and Large Video Dataset

Abstract: In this paper, we study the subsequence matching problem of near-duplicate video detection. In particular, we address the application of monitoring a continuous stream with a large video dataset. To achieve real-time response and high accuracy, we propose a novel framework containing two characteristics. First, the subsequence matching is transformed to a 2-D Hough space projection of pairwise frame similarities between two subsequences. We present an approximate Hough transform that replaces the 2-D Hough spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…In order to achieve higher network utilization, big-file transfer based on multi-path routing has attracted significant attention, particularly for resource-limited networks [8,9] . Multi-path file transfer problems encompass both the single-file multi-path transfer problem [10][11][12] and the multi-file multi-path transfer problem [13][14][15][16] . However, most of previous works do not consider the size of files and how to search for a path set in a given network.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve higher network utilization, big-file transfer based on multi-path routing has attracted significant attention, particularly for resource-limited networks [8,9] . Multi-path file transfer problems encompass both the single-file multi-path transfer problem [10][11][12] and the multi-file multi-path transfer problem [13][14][15][16] . However, most of previous works do not consider the size of files and how to search for a path set in a given network.…”
Section: Introductionmentioning
confidence: 99%
“…For these incremental databases, topic extraction algorithms such as pLSA and LDA, have a computational burden too heavy to recompute topics each time the databases increase their size with new samples. In other kinds of applications, some authors [24] have shown the advantages of considering an incremental scenario to manage large video collections in an efficient way, therefore this scheme may help us to improve the topic extraction task. In this work, we are interested in exploring whether video retrieval performance is affected by the use of different topic models and how video retrieval systems based on topic models are able to efficiently manage these incremental databases.…”
mentioning
confidence: 99%
“…, and Chang-Su Kim [3,4] 은 오직 유사중복 구간의 유무만을 결정한다. 반면에 다 이나믹 프로그래밍(dynamic programming)을 기반으로 최 적화 문제를 해결함으로써 더욱 정밀한 프레임 단위의 정 합을 가능하게 하는 기법들도 연구되고 있다 [5][6][7] .…”
unclassified